(untitled) (Revista do Centro de Estudos Portugueses, 2021)
Abstract: Here we discuss editorial agency and its impact in the work of Fernando Pessoa, focusing on perception, mobility and interpretation. A posthumous publication is a privileged object to investigate the complexity of the process of editorial agency and its effects because, in the posthumous extension of a corpus, what is at stake is precisely its construction. We also examine the role of the editor and his intervention, rather than the one of publishers, bearing into account the impact the decisions and reorganizations can have when speaking of posthumous works. We conclude that a “work” is the product, or the result, of the joint work left by an author and that of its editors, and that a work or a set of works is not something determined and established forever, but a reassembled product, or the result of a construction or reconstruction. Keywords: Fernando Pessoa; editorial agency; mobility; interpretation; work; posthumous work. Resumo: Discutimos aqui a mediação editorial e o seu impacto na obra de Fernando Pessoa, com enfoque na perceção, na mobilidade e na interpretação. Uma publicação póstuma é um objeto privilegiado para investigar a complexidade do processo de mediação editorial e os seus efeitos porque, na extensão póstuma de um corpus, o que está em jogo é precisamente a sua construção. Analisamos também o papel do editor (editor) e da sua intervenção, em vez do papel da editora (publisher), tendo em consideração o impacto que as decisões e as reorganizações podem ter quando falamos de obras póstumas. Concluímos que uma “obra” é o produto, ou o resultado, do trabalho, em conjunto, do autor e da obra que deixou, e dos editores; e que uma obra ou um conjunto de obras não é algo determinado ou estabelecido para sempre, mas um produto reorganizado, ou o resultado de uma construção ou reconstrução. Palavras-chave: Fernando Pessoa; mediação editorial; mobilidade; interpretação; obra; obra póstuma.